Does Implant-Abutment Interface affect Marginal Bone Levels around Implants? - Elemek, Eser; Urgancioglu, Artun; Dincer, Janberd; Cilingir, Altug (European Journal of Dentistry, 2019)
Objective The use of dental implants with different types of surface roughness and implant-abutment interface has brought about a situation of marginal bone loss. Therefore, the aim of this study was to analyze and compare marginal bone levels of different types of osseointegrated dental implants with platform switch (Group A: Ankylos, Mannheim, Germany) and platform match (Group B: Dentsply Xive, Mannheim, Germany, and Group C: MIS Implant Technologies, Karmiel, Israel).Materials and Methods One hundred and seven patients (52 men and 55 women) with a mean age of 54.79 (standard deviation ± 12.35) years and a total of 321 dental implants (Group A, n = 198; Group B, n = 58; and Group C, n = 65) placed in a private practice between April 2006 and May 2015 were retrospectively analyzed. In addition to demographic information and implant characteristics, marginal bone levels were evaluated by Image J (Wayne Rasband, National Institute of Health, Maryland) program.Results The mean age of all patients was 54.79 ± 12.35 years, and 51.5% of them were women. Implants supporting fixed bridge were most commonly used in all groups (65%), whereas only 20% were restored with a single crown and 15% with overdentures. In total, 47.5% of all implants showed no marginal bone loss. Mean bone loss in Group A was significantly lower (0.81 ± 1.60 mm) as compared to Group B (1.58 ± 1.59 mm) and Group C (1.18 ± 1.36) (p < 0.005).Conclusion Among different types of dental implants, platform switch seems to preserve marginal bone levels and increase the long-term success of dental implants.
Keywords: implant; marginal bone loss; platform match; platform switch